Wegen Corona allein zu Haus: Psychosoziale Folgen der Isolation während des Lockdowns für Alleinlebende - Muckenhuber, Johanna; Kölbl, Max (Tectum Verlag, 2023)
How did the contact restrictions and lockdowns in the course of the containment of the COVID-19 pandemic affect people living alone? The authors of this anthology analyse that situation and present not only the functions of social contact that can be replaced by virtual communication, but also those aspects which are essen-tially tied to face-to-face contact in one place. They pay special attention to the effects of the restrictions on different age and population groups. The analyses are based on quantitative statistical analyses by the Austrian Corona Panel, on the analysis of qualitative interviews with people living alone and on the analysis of interviews.With contributions byStephanie Bacher | Miriam Burkia Stocker | Martina Frei | Christof Hradetzky | Max Kölbl | Johanna Muckenhuber